Exocyst-positive organelles and autophagosomes are distinct organelles in plants - Lin, Youshun; Ding, Yu; Wang, Juan; Shen, Jinbo; Kung, Chun Hong; Zhuang, Xiaohong; Cui, Yong; Yin, Zhao; Xia, Yiji; Lin, Hongxuan; Robinson, David G.; Jiang, Liwen (Plant physiology, 2015)
Autophagosomes are organelles that deliver cytosolic proteins for degradation in the vacuole of the cell. In contrast, exocyst-positive organelles (EXPO) deliver cytosolic proteins to the cell surface and therefore represent a form of unconventional protein secretion. Because both structures have two boundary membranes, it has been suggested that they may have been falsely treated as separate entities. Using suspension culture cells and root tissue cells of transgenic Arabidopsis (Arabidopsis thaliana) plants expressing either the EXPO marker Arabidopsis Exo70E2-GFP or the autophagosome marker yellow fluorescent protein (YFP)-autophagy-related gene 8e/f (ATG8e/f), and using specific antibodies against Exo70E2 and ATG8, we have now established that, in normally growing cells, EXPO and autophagosomes are distinct from one another. However, when cells/roots are subjected to autophagy induction, EXPO as well as autophagosomes fuse with the vacuole. In the presence of concanamycin A, the punctate fluorescent signals from both organelles inside the vacuole remain visible for hours and overlap to a significant degree. Tonoplast staining with FM4-64/YFP-Rab7-like GTPase/YFP-vesicle-associated membrane protein711 confirmed the internalization of tonoplast membrane concomitant with the sequestration of EXPO and autophagosomes. This suggests that EXPO and autophagosomes may be related to one another; however, whereas induction of autophagy led to an increase in the amount of ATG8 recruited to membranes, Exo70E2 did not respond in a similar manner.